INFLUENCE OF MODIFICATION AND HEAT TREATMENT ON MICROSTRUCTURE AND IMPACT TOUGHNESS OF LOW ALLOY WHITE CAST IRON - LI YongLi; TANG XiuLi (Jixie qiangdu)
By modification and heat treatment,analyzed from all aspects of microstructure,hardness and impact toughness through three kinds of modifiers for low-alloy white cast iron. Experimental results showed that modification could change the morphology and distribution of low alloy white cast iron,it also could enhance that’s continuity of the matrix and the toughness of the material,and the Zn + Ca-Si + Nb modification have the best effect,normalizing treatment after modification can further improve performance.